Análise da eficiência de custos na produção de café arábica em relação à rentabilidade e produtividade - Cunha, Mariene Resende (2021)
The present research had as main objective to analyze the main Arabica coffee producing regions in Brazil, in the period between the years 2008 and 2018, focusing on production costs related to the productivity and profitability of crops. The study was based on theories of production and production costs. The research is identified as quantitative, descriptive and applied. For statistical analysis, descriptive statistics and the Data Envelopment Analysis (DEA) technique were used, oriented to inputs and outputs, using the CCR (CHARNES, COOPER and RHODES, 1978) and BCC (BANKER, CHARNES and COOPER, 1984) models. Production costs, productivity and profitability were detailed for the seven analyzed regions of Brazil: Cristalina (GO), Franca (SP), Londrina (PR), Luis Eduardo Magalhães (BA), Patrocínio (MG), São Sebastião do Paraíso (MG) and Venda Nova do Emigrante (ES), according to the types of mechanized, semi-mechanized, manual and irrigated cultivation, with data extracted from the platform of the National Supply Company (CONAB). Through the analysis of technical efficiency, we sought to analyze and point out the necessary cost reductions related to waste and scale efficiency when presenting which units operate on an optimal scale, with better productivity and profitability. As a result, the regions that presented the greatest efficiency highlights were Franca and Londrina, which were presented as benchmarks by the CCR model, the first also being a reference by the BCC model, together with Luis Eduardo Magalhães. Therefore, in the inefficiency aspect, the region of São Sebastião do Paraíso, in semi-mechanized and mechanized crops, presented poor results in terms of crop management. It should be noted that the density of the soil, the crop cultivation system, from manual to mechanization and irrigation, fruit harvesting and the amount of fertilizers used interfere with the cost of coffee. It was possible to observe a highlight related to the use of machines and equipment in cultivation, in addition to the use of technology, factors that can provide greater productivity, better quality and management and, consequently, better profitability. However, when not properly managed, they cause important negative returns for the rural producer, making it of fundamental importance to relate theory to practice in crop management.